2021
DOI: 10.3390/app11114862
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Mechanical, Tribological, and Fricative Reduction Properties of Pure Titanium by Boriding

Abstract: Surface boriding of pure titanium was performed using dissolved salt impregnation to modify the surface hardness and improve wear performance. The effect of boriding temperature (950–1150 °C) on the microstructure, composition, and room-temperature tribological properties of the borided samples was investigated by X-ray diffraction, scanning electron microscopy, and ball-on-disc tribometry, respectively. Gibbs free energy was also calculated to evaluate the compounds generated during the boriding at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This is also consistent with the boronizing kinetics studies, which confirmed the diffusive nature of boronizing. It was found that boronizing obeys the parabolic law where the square of the layer thickness is proportional to the duration of boronizing, and the proportionality coefficient represents the growth rate constant [ 1 , 4 , 5 , 7 , 9 , 13 , 24 , 30 , 32 , 39 , 40 ]. Since boronizing obeys the parabolic law, this would imply that diffusion slows down over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also consistent with the boronizing kinetics studies, which confirmed the diffusive nature of boronizing. It was found that boronizing obeys the parabolic law where the square of the layer thickness is proportional to the duration of boronizing, and the proportionality coefficient represents the growth rate constant [ 1 , 4 , 5 , 7 , 9 , 13 , 24 , 30 , 32 , 39 , 40 ]. Since boronizing obeys the parabolic law, this would imply that diffusion slows down over time.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hardness, previous studies on the cross-sectional hardness of boride layers determined the hardness as the arithmetic mean of five or more measurements at each depth [ 2 , 3 , 4 , 5 , 9 , 37 , 39 ]. This method is suitable for layers parallel to the surface, and it can be said that reliable results are obtained in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Methods that improve the integrity of the surface and at the same time reduce the coefficient of friction between the contacting surfaces can be included among the options that allow the reduction of the coefficient of friction and the reduction of the thermal load. This includes options such as surface hardening, chemical-heat treatment (carburizing, nitriding and boriding), laser welding, laser texturing and, finally, coating (PVD, CVD) and others [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, its hardness and wear resistance are low, which limits its use. Various processing methods, including severe plastic deformation [16][17][18], thermal oxidation [19][20][21], carburization [22][23][24], nitriding [7,25,26], and boriding [7,27,28], have been proposed to improve its mechanical properties. During the processes of thermal oxidation, carburization, nitriding, and boriding, the atom diffusion behavior in pure titanium plays a key role in achieving good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%